Presneti čaj - Strnad, Janez (Obzornik za matematiko in fiziko, 2010)
It is annoying when pouring tea from a teapot the liquid misses the cup. Detailed observations of the phenomenon lead to interesting insight concerning the flow of fluids.
Keywords: Coandov pojav; fizika; tekočine; tekočinski tok